Mentálny „koridor“ mediálnej spoločnosti: fascinácia zábavou - Pravdová, Hana (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2012)
In the paper the author points out current life-style trends, which are largely influenced by the mass media and the entertainment industry. In the course of two centuries, the mass media and the entertainment sector have become important factors in shaping the mentality of post- -modern society. The aim of the article is to analyze the phenomenon of media entertainment which has become an indispensable part of contemporary society’s everyday life. People are fascinated by entertainment because it gives them pleasure, experience, cultural competences but also allows to escape from reality.